Factors affecting women entrepreneurs' success: A study of small- and medium-sized enterprises in emerging market of Pakistan - Rizwan Ullah Khan; Yashar Salamzadeh; Syed Zulfiqar Ali Shah; Mazhar Hussain (Journal of Innovation and Entrepreneurship, 2021)
In the present era, women are recognized as successful entrepreneurs through their strong desire, qualities, and capabilities for robust economic development. Due to such an important contribution of women in economic development, we propose to investigate the factors which affect women entrepreneur's success in Pakistan. Data were collected through structured questionnaires from 181 registered SMEs operating in Pakistan. A conceptual model is developed, while SPSS and AMOS software's are used for analysis. The results indicate that the internal factors including the need for achievements, risk-taking, and self-confidence and external factors including economic factors and socio-cultural factors have a positive and significant influence on the success of women-owned enterprises. This research recommends Small and Medium Enterprises Development Authority (SMEDA), policymakers, and practitioners to encourage women entrepreneurs to run their businesses for the long term by providing a variety of incentives and supports related to those internal and external factors. Numerous studies have been conducted to test the different factors' effects on women's entrepreneurial success, but our study investigated some psychological, cultural, and religious factors that are still almost untouched especially in Pakistan. The current study also contributes to the existing literature through empirical shreds of evidence.
Keywords: 650; Economic factors; Entrepreneurial success; Islamic Republic of Pakistan; Need for achievement; Risk taking; Socio-cultural factors; Women